Studies on reduction behaviour of highly fluxed iron ore pellets for application in steelmaking - Dishwar R.K.; Mandal A.K.; Sinha O.P. (My University, 2025)
The present study concentrates on investigation of the possibilities of making high basicity reduced iron ore pellets (DRI) at low cost, which can be further used in the pig iron refining or steel making technology in EAF/LD Converter process. The reduction behaviour of high flux (basicity 2, 4, 6 & 8) hardened iron ore pellets, reduced at temperature (900-1050°C) were examined and reported here. Result showed temperature and basicity both influenced the reduction behaviour of iron ore pellets. Evolution or dissolution of different phases during reduction studied with the help of XRD and SEM. © 2021 Elsevier Ltd. All rights reserved.